1988
DOI: 10.1002/gj.3350230401
|View full text |Cite
|
Sign up to set email alerts
|

The arenig in South Wales: Sedimentary and volcanic processes during the initiation of a marginal basin

Abstract: Marine clastic sediments and volcanics of Arenig (Ordovician) age crop out in South Wales. These were deposited after presumed late Tremadoc erosion and subsequent arc volcanicity. Arenig sedimentation was transgressive, and followed significant erosion of the arc volcanics. Arenig conglomerates, sandstones, and mudstones were deposited in deltaic and turbiditic systems. Storm and tidal processes influenced the shallow marine deposits. The minor rhyolitic volcanics extruded during the Arenig reflect the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Fortey and Owens (1987) postulated that the subsequent development of a probable barrier to circulation further west, during deposition of the Cwmffrⓦd and Cwm yr Abbey members, then produced a stagnant basin with restricted circulation in the Carmarthen region. This interpretation was augmented by Traynor’s (1988) investigation of sedimentary processes during deposition of the Arenig Series in South Wales, which concluded that the Arenig deposits across South Wales were ponded in small interconnected marine sub-basins with facies and facies distributions controlled by intra-Arenig tectonic activity during an overall sea-level rise. Graptolites first become locally numerous in the Afon Ffinnant, Blaencediw and Colomendy formations, with species of Azygograptus and Expansograptus , and together with cyclopygid trilobites bring the first indications of oceanic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortey and Owens (1987) postulated that the subsequent development of a probable barrier to circulation further west, during deposition of the Cwmffrⓦd and Cwm yr Abbey members, then produced a stagnant basin with restricted circulation in the Carmarthen region. This interpretation was augmented by Traynor’s (1988) investigation of sedimentary processes during deposition of the Arenig Series in South Wales, which concluded that the Arenig deposits across South Wales were ponded in small interconnected marine sub-basins with facies and facies distributions controlled by intra-Arenig tectonic activity during an overall sea-level rise. Graptolites first become locally numerous in the Afon Ffinnant, Blaencediw and Colomendy formations, with species of Azygograptus and Expansograptus , and together with cyclopygid trilobites bring the first indications of oceanic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The base of the middle Arenig Whitlandian Stage is placed 40 m above the base of the Afon Ffinnant Formation (Fortey & Owens, 1987, p. 87). Traynor (1988) assigned the Ogof Hên Formation to his facies 3, comprising fluviodeltaic deposits. The mudstones of the Pibwr and Cwm yr Abbey members are placed in facies 6 (deep water mudstone), and the Cwmffrŵd Member and Afon Ffinnant Formation are placed in facies 5, representing deep water sediment-gravity flows in which turbidites are interbedded with facies 6 mudstone (Traynor, 1988).…”
Section: A Carmarthen Areamentioning
confidence: 99%
See 1 more Smart Citation
“…A paleomagnetic result (Table 2) is available from volcanic rocks in the Treffgarne Formation, in SW Wales (Trench et al, 1992), which consists of andesitic flows overlain by marine volcaniclastic, possibly pyroclastic units, and has been correlated with similar Tremadocian volcanic arc rocks of the Rhobell volcanic complex below the Floian unconformity in the Harlech Dome area (Traynor, 1988). Paleomagnetic sample sites were taken along a moderately north-dipping section in quarries in Treffgarne Gorge, representing the andesite flows, a conglomerate with andesite clasts, and overlying purple and green mudstone.…”
Section: Welsh Basin -Cymru Terranementioning
confidence: 99%